Using Guided Imagery and Hypnosis in Brief Therapy and Palliative Care - Battino, Rubin (New York : Routledge, 2020)
Using Guided Imagery and Hypnosis in Brief Therapy and Palliative Care presents a model for effective single-session therapy. Chapters include more than a dozen case studies with transcripts and commentary. Readers will learn how to use an adapted model of Remen's healing circle for preparing patients for surgery, and guided imagery and other approaches are presented for enhancing palliative care. Extensive appendixes provide a wide variety of valuable tools that psychotherapists can use with clients concerned with end-of-life issues.
Forewords, Michael Hoyt, Trevor Silvester 1. Introduction: Expectation, the Placebo Effect, and Chatting 2. The Charlie Brown Exceptional Patient and Caregiver Group of Yellow Springs 3. Preparation for Surgery -- Two Approaches 4. Case Study 1 -- Mary and Anxiety and Insomnia and Shit and Einstein and.. 5. Case Study 2: Bobbi and Her Needy Knees 6. Guided Imagery for Healing and Psychotherapy 7. Case Study 3: Marvin and Weight Control and the Mighty M&Ms 8. Case Study 4: Carol and the Curious Cough 9. Rapport and the Therapeutic Alliance 10. Case Studies 5 & 6: Sammy and Self-Regard and Normalizing Norman 11. Case Study 6: Normalizing Norman 12. Healing Language 13. Case Study: Jennifer, Anxiety, Manzanita Beach and Jesus 14. Case Study 8: Barbara and Stress and Hearing and a Husband 15. Practical Matters 16. Case Study 9: Laura and Breaking Away 17. Case Study 10: George and Smoking 18. Case Study 11: Peter and His PA 19. Case Study 12: Gloria and the Oboe and Being Adequate 20. Case Study 13: Nonagenarian Charlie with Anxiety About Eye Problem 21. Chatting Revisited 22. Case Study 14: Joe and the NLP Fast Allergy Cure 23. Case Study 15: Joan and the NLP VK Dissociation Fast Phobia Cure 24. Healing Factors 25. Guided Imagery, Hypnosis and Other Approaches for Palliative Care 26. Extraordinary Sessions 27. Some Ending Thoughts and Comments Appendix A. Ruminations on Turning 88 Appendix B. End-of-Life Issues Appendix C. Questions for People in Their Dying Time Appendix D. Patient's Bill of Rights
OCLC-licensed vendor bibliographic record.
Keywords: Imagery (Psychology) -- Therapeutic use; Visualization -- Therapeutic use; Hypnotism -- Therapeutic use; Palliative treatment; MEDICAL / Allied Health Services / Hypnotherapy; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Hypnotism